Quality of Elementary Education in Himachal Pradesh An Evaluative Study - Raj, Hem; Garg, Mamta (JOURNAL OF INDIAN EDUCATION, 2019)
Quality education is the education that best fits the present and future needs of the learners in given circumstances and prospects. Quality education embraces the development of every student’s potential in every new generation. The present study aimed to examine the existing quality of elementary education in Himachal Pradesh state which came up as a unique example of success in India for its high literacy rate and access to elementary education. The Gross Enrolment Ratio, for both boys and girls across rural and urban areas, is consistently above 100. Despite the enhanced enrolments, many reports indicated poor quality of education here. In this study, investigators intended to find out whether students were being prepared for life, which is the aim of education as envisaged in RTE, 2009. To have an insight about this, other related quality indicators (input and process) were studied. Descriptive survey method with mixed approach (quantitative and qualitative) was used. The sample of study consisted of 17 schools from three districts of Himachal Pradesh. Both non-testing techniques (observations and focus group discussion) and psychological tests/questionnaires were employed as per the objectives of the study. The results indicated that the input indicators of quality, related with learners (intelligence and achievement motivation), teachers (qualification, status and attitude towards teaching) and school infrastructure, were of satisfactory level to a large extent in most of the schools, still learners’ outcome was not satisfactory. The unsatisfactory output may be attributed to the flawed input/process indicators, especially the modes of curriculum transactions which lacked child-centeredness.